Model Pengembangan Teknologi Pembelajaran Bahasa Arab di Era Digital: A Development Model of Technology for Arabic Language Learning in the Digital Era - Anisa Amalia Hazrah; Rodhy Harisca (AL-QIBLAH: Jurnal Studi Islam dan Bahasa Arab, 2026)
This study explores the discourse within the field of educational technology with a specific focus on the development of technology-based models for Arabic language learning in the digital era. The purpose of this research is to formulate a relevant and adaptive development model that supports modern learning demands for Arabic learners amid the rapid advancement of digital technologies. Employing a qualitative literature-based approach, this study analyzes theories of educational technology, instructional design models, and various digital implementations in Arabic language learning. Data were analyzed through reduction, classification, and synthesis to produce coherent conceptual patterns. The findings indicate that an effective development model in the digital era must integrate interactive multimedia, flexible online platforms, personalized learning, and strong support for self-directed learning. The contribution of this study lies in presenting a conceptual model that can serve as a reference for educators, researchers, and media developers in designing more innovative and contextual Arabic learning technologies. This study highlights the strategic role of educational technology in improving the quality of Arabic language learning in the digital era.